A BIM-based framework for evacuation assessment of high-rise buildings under post-earthquake fires. (November 2021) - Lotfi, Nafiseh; Behnam, Behrouz; Peyman, Farzad
Abstract: Recent experiences have shown that post-earthquake fires (PEF) can be catastrophic; they should hence receive special attention at both urban and building scales. In this article, a 28-floor high-rise multipurpose building is examined under PEFs to monitor whether the building can provide a safe evacuation environment for its inhabitants. The monitoring process is framed using building information modeling (BIM) which is a capable tool for providing comprehensive information for different operators as per their duties. Using Pyrosim, the escape routes' workability during a PEF is measured. As well, the smoke and fire developments on different floors are all simulated. It is shown that it takes around 400–600 s different floors to fill up with smoke and toxic gases. Results from the fire and smoke simulations, and 3D modeling of the building show that the building cannot meet a guaranteed evacuation plan; hence, it is necessary to add further appropriate equipment. Employing manual equipment is proposed here to cope with a PEF situation when many of the buildings' automatic facilities and established urban infrastructure may not be available. Due to the chaotic situation of PEF in urban areas, the proposed framework here can be deliberated as a practical model for evacuation assessment of occupants in high-rise buildings; either for designed ones or those that are yet to be designed. Highlights: A BIM-based framework is proposed for evacuating inhabitants from tall buildings under PEF. CFD-based modeling is employed for smoke and fire simulation. Workability of escape paths in the case studied is controlled to monitor whether a safe evacuation is guaranteed. Mitigation strategies are adopted to reduce the associated PEF risks in tall buildings.